2022
DOI: 10.3390/antibiotics11050542
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Antibiotic Resistance on Innate Immune Responses to Staphylococcus aureus Infection

Abstract: Staphylococcus aureus (S. aureus) causes a broad range of infections and is associated with significant morbidity and mortality. S. aureus produces a diverse range of cellular and extracellular factors responsible for its invasiveness and ability to resist immune attack. In recent years, increasing resistance to last-line anti-staphylococcal antibiotics daptomycin and vancomycin has been observed. Resistant strains of S. aureus are highly efficient in invading a variety of professional and nonprofessional phag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 240 publications
0
3
0
Order By: Relevance
“…The well-characterized mutations that lead to antibiotic resistance are now revealing a new aspect: A dual function, in which these mutations also have an impact on immune effector mechanisms. This emerging evidence suggests that antibiotic resistance mutations not only protect bacteria from the effects of antibiotics but also have additional effects on how the immune system responds to infection and accomplishes immune evasion [ 4 ]. Studies have shown that the acquisition of certain point mutations in specific genes of daptomycin-resistant methicillin-resistant Staphylococcus aureus leads to a notable decrease in the secretion of proinflammatory cytokines, such as TNF-α, interleukin-6 (IL-6), and macrophage inflammatory protein-1β (MIP-1β), along with the attenuated expression of IL-1β, TNF-α, CXCL2, and CCL2 in MRSA biofilms [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The well-characterized mutations that lead to antibiotic resistance are now revealing a new aspect: A dual function, in which these mutations also have an impact on immune effector mechanisms. This emerging evidence suggests that antibiotic resistance mutations not only protect bacteria from the effects of antibiotics but also have additional effects on how the immune system responds to infection and accomplishes immune evasion [ 4 ]. Studies have shown that the acquisition of certain point mutations in specific genes of daptomycin-resistant methicillin-resistant Staphylococcus aureus leads to a notable decrease in the secretion of proinflammatory cytokines, such as TNF-α, interleukin-6 (IL-6), and macrophage inflammatory protein-1β (MIP-1β), along with the attenuated expression of IL-1β, TNF-α, CXCL2, and CCL2 in MRSA biofilms [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The immunological response of the host plays a vital role in the outcome of bacterial infections, yet the differences in host responses to antibiotic-resistant and susceptible bacteria remain poorly understood. Several factors may contribute to the differences in host responses to antibiotic-resistant and susceptible bacteria, including the virulence of the bacterial strain and host genetic factors [ 4 , 5 ]. Notably, emerging evidence suggests that a compromised immune status may not pose a risk factor for multi-drug resistant (MDR) bacterial infection as previously thought [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of antibiotics such as streptogramin, virginiamycin, florfenicol, and rifampicin over the last few decades has not solved the problem of antibiotic resistance but has rather exacerbated this crisis (Foster, 2017). More worryingly, resistance to cell membrane-targeting daptomycin and cell wall-targeting vancomycin, the last line of antibiotics against S. aureus, has successively emerged (Jahan et al, 2022;Yang et al, 2023). The first case of vancomycin-resistant Staphylococcus aureus was reported in Japan in 1997, followed by sporadic reports of daptomycin-and vancomycin-resistant strains (Humphries et al, 2013;Miller et al, 2016).…”
Section: Introductionmentioning
confidence: 99%